If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 38 = 6x + 6x + -10 Reorder the terms: 38 = -10 + 6x + 6x Combine like terms: 6x + 6x = 12x 38 = -10 + 12x Solving 38 = -10 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 38 + -12x = -10 + 12x + -12x Combine like terms: 12x + -12x = 0 38 + -12x = -10 + 0 38 + -12x = -10 Add '-38' to each side of the equation. 38 + -38 + -12x = -10 + -38 Combine like terms: 38 + -38 = 0 0 + -12x = -10 + -38 -12x = -10 + -38 Combine like terms: -10 + -38 = -48 -12x = -48 Divide each side by '-12'. x = 4 Simplifying x = 4
| 29=6 | | -11=p-17 | | 4x-6+5x=57 | | 9=3g | | 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 |